Приключения барона Мюнхаузена - Распэ Рудольф Эрих (Акцент, 1993)
Экземпляры: ф.4 (1994) / Инвентарный номер: 37489 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Р 24 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-442